Tolvaptan in the Management of Acute Euvolemic Hyponatremia After Transsphenoidal Surgery: A Retrospective Single-Center Analysis - Indirli, Rita; Ferreira de Carvalho, Júlia; Cremaschi, Arianna; Mantovani, Beatrice; Sala, Elisa; Serban, Andreea Liliana; Locatelli, Marco; Bertani, Giulio; Carosi, Giulia; Fiore, Giorgio; Tariciotti, Leonardo; Arosio, Maura; et al. (Frontiers in Endocrinology, 2021)
Introduction. Syndrome of inappropriate antidiuresis (SIAD) can be a complication of hypothalamus-pituitary surgery. The use of tolvaptan in this setting is not well established, hence the primary aim of this study was to assess the sodium correction rates attained with tolvaptan compared with standard treatments (fluid restriction and/or hypertonic saline). Furthermore, we compared the length of hospital stay in the two treatment groups and investigated the occurrence of overcorrection and side effects including osmotic demyelination syndrome. Methods. We retrospectively reviewed 308 transsphenoidal surgical procedures performed between 2011 and 2019 at our hospital. We selected adult patients who developed post-operative SIAD and recorded sodium monitoring, treatment modalities and outcomes. Correction rates were adjusted based on pre-treatment sodium levels. Results. Twenty-nine patients (9.4%) developed post-operative SIAD. Tolvaptan was administered to 14 patients (median dose 15 mg). Standard treatments were employed in 14 subjects (fluid restriction n=11, hypertonic saline n=1, fluid restriction and hypertonic saline n=2). Tolvaptan yielded higher adjusted sodium correction rates (12.0 mmolL-1/24h and 13.4 mmolL-1/48h) than standard treatments (1.8 mmolL-1/24h, p<0.001, and 4.5 mmolL-1/48h, p=0.004, vs. tolvaptan). The correction rate exceeded 10 mmolL-1/24h or 18 mmolL-1/48h in 9/14 and 2/14 patients treated with tolvaptan, respectively, and in no patient who received standard treatments. No side effects including osmotic demyelination occurred. Tolvaptan was associated with a shorter hospital stay (11vs.15 days, p=0.01). Conclusions. Tolvaptan is more effective than fluid restriction (with or without hypertonic saline) and allows for a shortened hospital stay in patients with SIAD after transsphenoidal surgery. However, its dose and duration should be carefully tailored and close monitoring is recommended to allow prompt detection of overcorrection.